Pengaruh Mediasi Information Avoidance pada penghentian penggunaan Social Network Service (SNS) - Muhammad Rayhan Ravandika; Diah Priharsari; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Social media is currently almost used by every individual to communicate with friends or collegues. During this pandemic, social media is also used as the main source of information. The ease of access to find information about COVID-19 is one of the reason why every social media user is the main choice to find news. However, the information about COVID-19 on social media is increase everyday and have some bad impact for its users. The impact for cause the users of social media those get too much information can take action to avoid information untul the termination of information sources. From the problem above, the researchers identified the effect of information overload on information avoidance until have an impact on termination. In addition, this study describes the mediating effect of information avoidance on the discontinuance use of social media. This study is using the SEM-CB method by distributing questionnaires to 322 respondents. From the results of the study, all of the hypotheses were accepted with a P-Value of 0,000 and individuals were partially mediated by performing information avoidance actions when experiencing information overload before decided to discontinuous the sources.